A comparison of qualitative and quantitative results concerning evaluations of co-branded offerings - Dickinson, Sonia; Heath, Tara (Palgrave Macmillian Lid., 2006)
This paper uses Aaker and Keller's (1990) brand extension model as a theoretical framework to examine the major factors contributing towards positive or negative evaluation of a co-branded offering. The study gained insights into how consumers form attitudes towards co-branded products using data from 194 university students in Western Australia. The research instrument measured reactions to 12 experimental co-brands and collected both qualitative and quantitative data. The findings suggest that when original brands are perceived as high quality then co-brands will be evaluated more positively, indicating that original brand attitudes (high quality levels) are more easily extended to co-brands. The research also found that if there was perceived 'fit' between participating co-brand partners (based on either product category or brand concept consistency) then the co-brand evaluation would be positive. Finally, it was found that the more difficult the product was to manufacture, the more favourable the co-brand evaluation, as the alliance seemed 'worthwhile'. The study recognises the importance that partner selection plays in the success of co-brands. It highlights the importance of original brand attitude (quality levels) and fit between brand partners for positive consumer evaluation in a co-brand context. This information can assist brand managers in decisions regarding partner brand selection.